2020
DOI: 10.1021/acsaem.0c00839
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Li-Rich Disordered Rocksalt Oxyfluoride Cathodes by Particle Surface Modification

Abstract: Promising theoretical capacities and high voltages are offered by Li-rich disordered rocksalt oxyfluoride materials as cathodes in lithium-ion batteries. However, as has been discovered for many other Li-rich materials, the oxyfluorides suffer from extensive surface degradation, leading to severe capacity fading. In the case of Li 2 VO 2 F, we have previously determined this to be a result of detrimental reactions between an unstable surface layer and the organic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…17,23 Most fluorination studies on DRX cathodes have been performed by (i) ball-milling DRX oxides with LiF or (ii) high-temperature solid-state reactions to form oxyfluoride compounds. 4,7,10 To counteract Li loss at high temperature, solid-state methods typically use excess Li precursors 9,17,20,24 which reduces efficiency. Although ballmilling does not require elevated temperatures, such processes are time consuming and difficult to scale.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,23 Most fluorination studies on DRX cathodes have been performed by (i) ball-milling DRX oxides with LiF or (ii) high-temperature solid-state reactions to form oxyfluoride compounds. 4,7,10 To counteract Li loss at high temperature, solid-state methods typically use excess Li precursors 9,17,20,24 which reduces efficiency. Although ballmilling does not require elevated temperatures, such processes are time consuming and difficult to scale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Richards et al reported that DRX and layered cathodes have different F solubilities, and in theory, the DRX structure creates TM-poor and lithium-rich local environments, which facilitate F – substitution. , Most fluorination studies on DRX cathodes have been performed by (i) ball-milling DRX oxides with LiF or (ii) high-temperature solid-state reactions to form oxyfluoride compounds. ,, To counteract Li loss at high temperature, solid-state methods typically use excess Li precursors ,,, which reduces efficiency. Although ball-milling does not require elevated temperatures, such processes are time consuming and difficult to scale.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering the coating layer is regarded as an efficient method to boost the comprehensive electrochemical performance of the LIBs. The coating layer is considered as the protective layer at the cathode/electrolyte interface: it strengthens the crystal structural stability and adjusts the interface chemistry to mitigate the TMs’ dissolution and other side reactions; it improve the Li + diffusion; and it further mitigates the cathode materials’ degradation and electrolyte decomposition. Therefore, many types of coating materials, including metal oxides, fluorides, and Li conductive metal oxides, have been exploited to improve electrochemical performance by impeding side reactions or improving electrical conductivity. Usually, nonelectrochemical active coating layer such as metal oxides, -fluorides, and -phosphates, in which the metal has no variational property, have been regarded as an efficient method to boost the comprehensive electrochemical property of the LRM oxide cathode materials. With regard to these coating layers, it mainly function as a defensive layer to mitigate the cathode materials degradation and the electrolyte decomposition.…”
Section: Challenges and Possible Solutions Of Li-rich Mn-based Oxide ...mentioning
confidence: 99%
“…[22][23][24][25][26] For Li-rich cathodes, such as the disordered rocksalt materials, to be harnessed for technological use, the mechanisms of O-redox that contribute to the hysteresis must be identified so that strategies to mitigate the loss of energy density can be found. [27][28][29][30][31][32][33][34][35] The disordered rocksalt cathode Li 2 MnO 2 F exhibits a large capacity comparable to that of Li-rich ordered layered oxides. [36,37] Previous studies using resonant inelastic X-ray scattering (RIXS) and density functional theory (DFT) have identified molecular O 2 formed and trapped within the bulk structure when charged to 4.8 V (approximately Li 0.75 MnO 2 F), with this process associated with the additional O-redox capacity.…”
Section: Introductionmentioning
confidence: 99%